2016
DOI: 10.13181/mji.v25i3.1407
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of persistent stress urinary incontinence at three months postpartum in Indonesian women

Abstract: Background: Mode of delivery and some certain risk factors have a relationship to postpartum stress urinary incontinence (SUI). For that reason, the objective of this study was to assess the prevalence of postpartum stress urinary incontinence (SUI), the relationship between postpartum SUI and mode of delivery; and the association between SUI and other demographic and obstetric factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The primary aim was to explore the association between preoperative factors and the occurrence of stress urinary incontinence (SUI) following hysterectomy, rather than establishing a causal relationship. 10 Univariate analysis focused on risk factors for SUI after laparoscopic hysterectomy. The study included 164 patients with benign non-prolapsed diseases who underwent the procedure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary aim was to explore the association between preoperative factors and the occurrence of stress urinary incontinence (SUI) following hysterectomy, rather than establishing a causal relationship. 10 Univariate analysis focused on risk factors for SUI after laparoscopic hysterectomy. The study included 164 patients with benign non-prolapsed diseases who underwent the procedure.…”
Section: Resultsmentioning
confidence: 99%
“…A onehour pad test in the study group indicated a mean urine leakage of 15.6 ± 2.3 g, with 60.7% of the patients having a significant degree of incontinence (more than 10 g). 10 In multivariate analysis, variables with statistical significance in the univariate analysis underwent Logistic multivariate analysis. Age, preoperative hemoglobin ≤ 100 g/L, preoperative urine bacteria ≥ 100u/L, uterine volume ≥ 90cm³, history of chronic cough, and BMI ≥ 28 kg/m² emerged as risk factors for postoperative urinary incontinence in patients undergoing hysterectomy (P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The reported prevalence of UI among women varies significantly across studies due to different definitions, the heterogeneity of diverse study populations, and population sampling procedures (Milsom, 2019) According to Fakhrizal et al, the prevalence of urge urinary incontinence among 400 postpartum primipara women ranges from 8.8 to 30%, with the likelihood of urinary incontinence increasing twofold in vaginal delivery versus cesarean delivery. Increased events are expected to follow the increase in the life expectancy of Indonesian women in the UI prevalence rate (Fakhrizal et al, 2016). To date, there has been no report on the overall prevalence of urinary incontinence and stress urinary incontinence (SUI) in Riau Province, one of Indonesia's coastal areas where most people work as fishermen and have low incomes.…”
Section: Introductionmentioning
confidence: 99%
“…3 The prevalence of SUI 3 months after delivery in Indonesia was estimated at 20.1%, while primiparous women with vaginal delivery had a 2.1 times higher risk of developing SUI. 4 Unfortunately, postpartum SUI treatment is still limited to lifestyle and pelvic floor rehabilitation. 5 The treatment of POP mostly starts when symptoms have already appeared, which only 5-20% of them, whereas almost half of women over 50 years of age with a history of vaginal birth have asymptomatic POP based on physical examination.…”
mentioning
confidence: 99%